1986
DOI: 10.1099/00221287-132-11-3137
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Taxonomic Study of Anaerobic Gram-negative Bacilli Classified as Bacteroides ureolyticus Isolated from Patients with Non-gonococcal Urethritis

Abstract: A numerical taxonomic study of 64 strains of anaerobic Gram-negative bacilli isolated from men with non-gonococcal urethritis, two unclassified laboratory strains of 'corroding bacilli', and 12 other strains of anaerobic Gram-negative bacilli, including nine received as anaerobic curved rods and three as 'Bacteroides corrodens' (B. ureolyticus), isolated from women with bacterial vaginosis, was undertaken. Seventeen reference anaerobic strains belonging to the genera Bacteroides, Fusobacterium, Mobiluncus, Mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This study showed that cell-free filtrates of C. ureolyticus cause a loss of ciliary activity through disruption and sloughing of the epithelial cells from the mucosal epithelium of human fallopian tubes and bovine oviduct organ cultures (9). Subsequently, studies by Fontaine et al suggested that these resultant cytopathic effects may be due to the existence of an unidentified membrane-bound endotoxin in the form of a lipopolysaccharide (LPS) (8)(9)(10). Interestingly, a number of studies have suggested that the proteolytic activity from proteases could be a contributing factor in the C. ureolyticus tissue damage observed in ulcerative and gangrenous lesions such as genital and perineal ulcers, decubitus and varicose lesions, and diabetic gangrene (4, 21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that cell-free filtrates of C. ureolyticus cause a loss of ciliary activity through disruption and sloughing of the epithelial cells from the mucosal epithelium of human fallopian tubes and bovine oviduct organ cultures (9). Subsequently, studies by Fontaine et al suggested that these resultant cytopathic effects may be due to the existence of an unidentified membrane-bound endotoxin in the form of a lipopolysaccharide (LPS) (8)(9)(10). Interestingly, a number of studies have suggested that the proteolytic activity from proteases could be a contributing factor in the C. ureolyticus tissue damage observed in ulcerative and gangrenous lesions such as genital and perineal ulcers, decubitus and varicose lesions, and diabetic gangrene (4, 21).…”
Section: Resultsmentioning
confidence: 99%
“…The bacteria has also been reported to be present in amniotic fluid and the genital tract of humans (5)(6)(7)(8). In addition, C. ureolyticus has commonly been isolated from patients suffering from periodontal disease, a disease which involves inflammatory and destructive conditions of the tissues surrounding the teeth (6).…”
mentioning
confidence: 99%
“…Whole-cell composition was examined by Py-MS in a Horizon Instruments PYMS 200X pyrolysis-mass spectrometer (Aries et al, 1986;Magee et al, 1989). Growth from 48-h cultures on blood agar was smeared on ironnickel alloy pyrolysis foils and heated rapidly in a vacuum to 530°C by the Curie point method.…”
Section: Pyrolysis-mass Spectrometry (Py-ms)mentioning
confidence: 99%
“…These include : buccal abscesses (Eiken, 1958) ; periodontal disease (Khairat, 1967 ;Duerden et al, 1987) and other oral infections (Schroter and Stawru, 1970;Duerden et al, 1982); soft tissue infection and ulcers, especially peripheral (e.g., varicose) ulcers and gangrene, and ulcerative conditions of the perineum and external genitalia (Labbt: et al, 1977;Duerden et al, 1982;Masfari et al, 1983Masfari et al, , 1985. Fontaine et al (1982,1984) used refined anaerobic transport and culture methods to isolate strains, subsequently confirmed as B. ureolyticus (Fontaine et al, 1986;Taylor et al, 1986) from urethral samples from men with non-gonococcal, non-chlamydia1 urethritis ; successful treatment with metronidazole further supported a pathogenic role for B. ureolyticus in these patients (Hawkins et al, 1988). Taylor et al (1987) examined isolates from urethritis and other conditions by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) of protein extracts and by conventional biochemical tests ; they concluded that strains from the various sources were similar but were able to divide the species into four types on the basis of SDS-PAGE patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Another of the genera associated with bacterial vaginosis, the gram-negative Bacteroides spp. also releases lipopolysaccharide, resulting in the sloughing of Fallopian tube epithelial cells and loss of ciliary activity within the Fallopian tubes (Fontaine et al 1986).…”
Section: Anaerobic Bacteriamentioning
confidence: 99%